Meningkatkan Profesionalisme Guru: Sebuah Harapan - Ali Muhson (Jurnal Ekonomi dan Pendidikan, 2004)
The teacher professionalism had to be improved because the teacher had the important roles to improve human resources quality. The several efforts can be done by the teacher is understanding the minimum standard of the profession, completing the teacher qualifications and competencies, creating the good partnership, improving the service-based working, and improving the creativity in use the very latest information and communication technologies. The improving of the teacher welfare supported the several efforts to improve the teacher professionalism.